2015
DOI: 10.1111/ics.12270
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of urban pollution upon skin status. A controlled study in Shanghai area

Abstract: This study demonstrated a significant impact of the pollution upon the skin status, as illustrated by changes in superficial biochemical parameters and volunteers' perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 18 publications
(27 reference statements)
1
68
0
1
Order By: Relevance
“…The skin surface lipid (SSL) film, a mixture of sebum and keratinocyte membrane lipids, is the first barrier against environmental stress [134]. Among the ingredients of SSL, squalene, a key biosynthetic precursor of cholesterol secreted by SGs, and α-tocopherol (vitamin E) secreted together with lipids from sebaceous gland, provide collaboratively antioxidant protection to the skin surface [135][136][137]. In addition, the by-products, squalene peroxides, produce during squalene oxidation, are considered to be involved in inflammatory and immunologically determined skin diseases, such as acne, atopic and seborrheic dermatitis as well as in skin cancerogenesis [138].…”
Section: Sebaceous Glands and Skin Skin Detoxificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin surface lipid (SSL) film, a mixture of sebum and keratinocyte membrane lipids, is the first barrier against environmental stress [134]. Among the ingredients of SSL, squalene, a key biosynthetic precursor of cholesterol secreted by SGs, and α-tocopherol (vitamin E) secreted together with lipids from sebaceous gland, provide collaboratively antioxidant protection to the skin surface [135][136][137]. In addition, the by-products, squalene peroxides, produce during squalene oxidation, are considered to be involved in inflammatory and immunologically determined skin diseases, such as acne, atopic and seborrheic dermatitis as well as in skin cancerogenesis [138].…”
Section: Sebaceous Glands and Skin Skin Detoxificationmentioning
confidence: 99%
“…In addition, the by-products, squalene peroxides, produce during squalene oxidation, are considered to be involved in inflammatory and immunologically determined skin diseases, such as acne, atopic and seborrheic dermatitis as well as in skin cancerogenesis [138]. A recent study in China showed that the urban polulation has a lower squalene/lipid ratio than the rural one, which may mean that reduction of squalene is induced by environmental pollutants [137]. Moreover, squalene peroxides are proposed as a reliable marker of environmental pollutants in the skin [138].…”
Section: Sebaceous Glands and Skin Skin Detoxificationmentioning
confidence: 99%
“…In this regard, it is of interest that: (i) greasy skin was reported to be more frequent in individuals living in a Chinese metropolitan area as compared with a nonpolluted area [7], (ii) in subsequent studies sebum levels were indeed found to be increased in individuals living in major cities with high pollution levels [8], and (iii) the sebum of these individuals was qualitatively altered [8]. Overall, these studies indicate the possibility that air pollution may contribute to the aggravation of acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…As leaves of certain trees may be used as markers of aerial pollution, in addition to global air analysis , human hairs could also be considered, by analogy, as airborne pollution probes. From a practical viewpoint, comparing the presence of PM and/or metals present on the hair surface of subjects living in two very different environments (low vs. severely polluted) seems a pertinent and important approach, in line with the objective(s) of the skin studies previously mentioned .…”
Section: Discussionmentioning
confidence: 96%